2014
DOI: 10.1039/c3cc47898j
|View full text |Cite
|
Sign up to set email alerts
|

Better understanding of mechanochemical reactions: Raman monitoring reveals surprisingly simple ‘pseudo-fluid’ model for a ball milling reaction

Abstract: Quantitative monitoring of a mechanochemical reaction by Raman spectroscopy leads to a surprisingly straightforward second-order kinetic model in which the rate is determined simply by the frequency of reactive collisions between reactant particles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(112 citation statements)
references
References 20 publications
(3 reference statements)
6
100
1
5
Order By: Relevance
“…Ma et al recently described a milling reaction mechanism based on thorough stirring of very small solid particles. 38 We have observed in agreement with the literature that the reaction speed could be easily increased by increasing the applied frequency. Furthermore, the diffusion rate in liquid assisted grinding reactions is higher than in dry ones.…”
Section: Mechanistic Studiessupporting
confidence: 92%
“…Ma et al recently described a milling reaction mechanism based on thorough stirring of very small solid particles. 38 We have observed in agreement with the literature that the reaction speed could be easily increased by increasing the applied frequency. Furthermore, the diffusion rate in liquid assisted grinding reactions is higher than in dry ones.…”
Section: Mechanistic Studiessupporting
confidence: 92%
“…for milling at 30 Hz was about 4.1 % min -1 , while for 20 Hz it was 0.7 % min -1 . The accelerating effect of a higher milling frequency on the reaction rate has been shown before 32 and is related to better mixing of the reactants and removal of the product from the reactant interface. Furthermore, milling with a higher frequency may introduce higher energy to the reaction system by creating crystal defects, strains and reducing the average particle size 28,29 .…”
Section: Structural Considerations Of the Isoniazid-benzoic Acid Cocrmentioning
confidence: 85%
“…These observations led the authors to propose a ''pseudo-fluid'' model of the reaction mixture under mechanochemical conditions, in which the reaction rate for this particular mechanochemical process is controlled largely by the number of reactive encounters involving surfaces of reactant imidazole and zinc oxide particles, and in which the role of milling is principally to stir the reaction mixture and expose fresh reactant surfaces by abrasion. 100 One of the most surprising aspects of such a pseudo-fluid reaction model, which was experimentally confirmed by conducting the reaction at different temperatures, is that the reaction rate is highly dependent only on the milling frequency (Figure 7.13d), but not temperature. That mechanochemical milling reactions by LAG and ILAG can indeed proceed in a manner that resembles established first-and second-order rate laws in solution was subsequently confirmed by the Halasz and Friščić groups by quantitative in situ and real time reaction monitoring using synchrotron X-ray diffraction.…”
Section: Stepwise Analysismentioning
confidence: 82%
“…As a faster alternative to X-ray powder diffraction, the James group has applied Raman spectroscopy to monitor the mechanochemical LAG reaction of zinc oxide and imidazole in the presence of DMF to form the microporous framework known as ZIF-6. 100 This kinetic study revealed that product formation proceeds in a manner that highly resembles the kinetics of a second-order reaction in solution. These observations led the authors to propose a ''pseudo-fluid'' model of the reaction mixture under mechanochemical conditions, in which the reaction rate for this particular mechanochemical process is controlled largely by the number of reactive encounters involving surfaces of reactant imidazole and zinc oxide particles, and in which the role of milling is principally to stir the reaction mixture and expose fresh reactant surfaces by abrasion.…”
Section: Stepwise Analysismentioning
confidence: 97%